Allograft Reconstruction of Chronic Tibialis Anterior Tendon Ruptures. (October 2015) - Huh, Jeannie; Boyette, Deanna M.; Parekh, Selene G.; Nunley, James A.
Background: Chronic ruptures of the tibialis anterior tendon are often associated with tendon retraction and poor-quality tissue, resulting in large segmental defects that make end-to-end repair impossible. Interpositional allograft reconstruction has previously been described as an operative option in these cases; however, there are no reports of the clinical outcomes of this technique in the literature. Methods: Eleven patients with chronic tibialis anterior tendon ruptures underwent intercalary allograft recon-struction between 2006 and 2013. Patient demographics, injury presentation, and details of surgery were reviewed. Postoperative outcomes at a mean follow-up of 43.8 (range, 6-105) months included the American Orthopaedic Foot & Ankle Society (AOFAS) Ankle-Hindfoot score, Short Form–12 (SF-12) physical health score, Lower Extremity Functional Score (LEFS), visual analog scale (VAS) pain rating, dorsiflexion strength, gait analysis, and complications. Results: The average postoperative dorsiflexion strength, as categorized by the Medical Council grading scale, was 4.8 ± 0.45. The average postoperative VAS score was 0.8 ± 1.1. The average LEFS was 66.9 ± 17.2, SF-12 physical health score was 40.1 ± 14.4, and AOFAS score was 84.3 ± 7.7. One complication occurred, consisting of transient neuritic pain in the superficial peroneal nerve distribution. There were no postoperative infections, tendon reruptures, reoperations, or allograft-associated complications. Conclusion: Allograft reconstruction of chronic irreparable tibialis anterior tendon ruptures yielded satisfactory strength, pain, and patient-reported functional outcomes. This technique offers a safe and reliable alternative, without the donor site morbidity associated with tendon transfer or autograft harvest. Level of Evidence: Level IV, retrospective case series.